A compensation approach for nonlinear gimbal axis drift of a control moment gyroscope. (April 2018) - Lee, S.D.; Jung, S.
Abstract: This paper investigates the axial drift phenomenon of a gimbal system of a Control Moment Gyroscope (CMG) system and proposes a solution to tackle the problem. A CMG is an indirect actuator to generate a torque in the desired direction by using a gyroscopic effect for the attitude control of dynamical systems. CMGs are easily subject to drift gradually against one direction resulting in the instability of the system. The fast repositioning control of the gimbal axis to the origin should be ensured to maximize the induced gyroscopic force. Since the position control for repositioning the gimbal axis takes time, the axial drift compensator is designed for the nonlinear drift model in the inverse dynamic control framework to shorten the repositioning time. Comparison studies with disturbance observer (DOB)-based control scheme are conducted to the same problem. Advantages and disadvantages of the proposed scheme are analysed. Experimental studies confirm that the proposed compensation method can dramatically improve the performances of the returning time to the origin and the torque regulation by compensating for the axial drift of the gimbal system compared with the conventional position control.